2006
DOI: 10.1007/s11095-006-0251-4
|View full text |Cite
|
Sign up to set email alerts
|

Saturable Absorptive Transport of the Hydrophilic Organic Cation Ranitidine in Caco-2 Cells: Role of pH-Dependent Organic Cation Uptake System and P-Glycoprotein

Abstract: Saturable absorptive transport of ranitidine in Caco-2 cells is partially mediated via a pH-dependent uptake transporter for organic cations and is subject to attenuation by P-gp. Inhibition and driving force studies suggest the uptake carrier exhibits similar properties to cloned human organic cation transporters. The results also imply ranitidine transport is not solely restricted to the paracellular space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
1
32
1
2
Order By: Relevance
“…Cimetidine has been reported to be a substrate for both P-gp and BCRP (Pavek et al, 2005;Taur and Rodriguez-Proteau, 2008), while ranitidine is transported primarily by P-gp (Collett et al, 1999;Bourdet and Thakker, 2006). Our results confirmed that cimetidine was a substrate of both P-gp and BCRP, as the efflux ratio was reduced to unity only in the MDR1/BCRP KO cell line, while ranitidine was identified as a substrate for P-gp alone.…”
Section: Discussionsupporting
confidence: 82%
“…Cimetidine has been reported to be a substrate for both P-gp and BCRP (Pavek et al, 2005;Taur and Rodriguez-Proteau, 2008), while ranitidine is transported primarily by P-gp (Collett et al, 1999;Bourdet and Thakker, 2006). Our results confirmed that cimetidine was a substrate of both P-gp and BCRP, as the efflux ratio was reduced to unity only in the MDR1/BCRP KO cell line, while ranitidine was identified as a substrate for P-gp alone.…”
Section: Discussionsupporting
confidence: 82%
“…To further characterize the transport across apical and basolateral membranes and investigate the possible contribution of carrier-mediated transporters, efflux and trans-stimulation efflux studies were performed (Zhang et al, 1999;Mizuuchi et al, 2000;Bourdet and Thakker, 2006). Figure 6 shows the directional efflux and demonstrates the effect of LY354740 and LY544344, present in the extracellular medium, on the efflux of [ 14 C]LY354740 amount.…”
Section: Varma Et Almentioning
confidence: 99%
“…[8,11,12] To provide insights into the uptake mechanism, the mean fluorescence, and accordingly the uptake/release of pyrene-R, as a function of concentration and time was monitored during incubation with [pyrene-R&1] 6 + and during chase (Figure 4). Figure 4 (top) shows that the uptake of the cage does not increase linearly with incubation time.…”
mentioning
confidence: 99%